Heterosis and Combining Ability in Complete Diallel Cross of Seven Chili Pepper Genotypes Grown in Ultisol - Dwi Wahyuni Ganefianti; Fahrurrozi Fahrurrozi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Ultisol is very promising area for Indonesian chili pepper production. This experiment aimed to determine General Combining Ability (GCA), Specific Combining Ability (SCA), heterosis and heterobeltiosis estimates of seven parental lines; A(KG1), B(KG2), C(KG3), D(KG4), E(KG5/UNIB-C-GTS1), F(KG6), and G(KG7) through full-diallel parental crosses. Experiment was conducted from July to November 2012 and designed in Randomized Complete Block with three replications. Results indicated that parent C(KG 3) had the highest GCA estimates for fruit length and fruit weight per plant. Parent F(KG6) had the highest fruit number per plant. Parents B(KG2), D(KD4) and G(KD7) had the highest GCA estimates for fruit diameter. Cross combinations C(KG3)xF(KG6) had the highest SCA estimates for fruit weight and fruit number per plant, whereas G(KG7)xC(KG3) and D(KG4)xG(KG7) had the highest SCA estimates for fruit length and fruit diameter. Cross combinations G(KG7)xC(KG3) and F(KG6)xC(KG3) had the highest heterosis and heterobeltiosis estimates for fruit weight per plant, whereas D(KG4)xB(KG2) and D(KG4)xE(KG5) had the highest heterosis and heterobeltiosis estimates for fruit number per plant. Cross combinations B(KG2)xE(KG5) and D(KG4)xG(KG7) had the highest heterosis and heterobeltiosis estimates for fruit length and fruit diameter. It is suggested that G(KG7)xC(KG3) and F(KG6)xC(KG3) are the most promising chili pepper hybrids grown in Ultisol.